Hydrogen isotopic differences between C3 and C4 land plant lipids: consequences of compartmentation in C4 photosynthetic chemistry and C3 photorespiration - Zhou, Y.; Grice, Kliti; Stuart-Williams, H.; Hocart, C.; Gessler, A.; Farquhar, G. (Wiley, 2016)
The 2H/1H ratio of carbon-bound H in biolipids holds potential for probing plant lipid biosynthesis and metabolism. The biochemical mechanism underlying the isotopic differences between lipids from C3 and C4 plants is still poorly understood. GC-pyrolysis-IRMS (gas chromatography-pyrolysis-isotope ratio mass spectrometry) measurement of the 2H/1H ratio of leaf lipids from controlled and field grown plants indicates that the biochemical isotopic fractionation (ε2Hlipid_biochem) differed between C3 and C4 plants in a pathway-dependent manner: ε2HC4 > ε2HC3 for the acetogenic pathway, ε2HC4 < ε2HC3 for the mevalonic acid pathway and the 1-deoxy-D-xylulose 5-phosphate pathway across all species examined. It is proposed that compartmentation of photosynthetic CO2 fixation into C4 mesophyll (M) and bundle sheath (BS) cells and suppression of photorespiration in C4 M and BS cells both result in C4 M chloroplastic pyruvate – the precursor for acetogenic pathway – being more depleted in 2H relative to pyruvate in C3 cells. In addition, compartmentation in C4 plants also results in (i) the transferable H of NADPH being enriched in 2H in C4 M chloroplasts compared with that in C3 chloroplasts for the 1-deoxy-D-xylulose 5-phosphate pathway pathway and (ii) pyruvate relatively 2H-enriched being used for the mevalonic acid pathway in the cytosol of BS cells in comparison with that in C3 cells.